2024
DOI: 10.1002/lary.31472
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of Patients Undergoing Evaluation of Possible Superior Canal Dehiscence

Ryan A. Bartholomew,
Marta M. Williams,
Brigette L. Wang
et al.

Abstract: ObjectiveTo characterize the diagnostic yield of patients undergoing evaluation for superior canal dehiscence syndrome (SCDS), and identify alternative conditions diagnosed in patients suspected of, but not ultimately diagnosed with, SCDS.MethodsDiagnostically undifferentiated adult patients suspected of having SCDS were identified between 2016 and 2021 at a tertiary academic medical system. Patients were categorized by diagnostic testing, radiographic superior semicircular canal (SSC) abnormality, symptoms, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[1][2][3] The symptom profile of SCDS overlaps with many other otologic and neurologic diseases, which when compounded with its rarity may lead to diagnostic delays. [4][5][6][7] Studies investigating the psychological burden of living with rare disease have found some may be associated with elevated rates of anxiety and depression. 8,9 Research evaluating psychiatric illness among patients with SCDS is limited to qualitative reports of associated depression and anxiety and one study demonstrating decreased health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The symptom profile of SCDS overlaps with many other otologic and neurologic diseases, which when compounded with its rarity may lead to diagnostic delays. [4][5][6][7] Studies investigating the psychological burden of living with rare disease have found some may be associated with elevated rates of anxiety and depression. 8,9 Research evaluating psychiatric illness among patients with SCDS is limited to qualitative reports of associated depression and anxiety and one study demonstrating decreased health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%